Exploration study of indigenous civet (Paradoxorus hermaphroditus) bacteria: isolates characterization and molecular identification - Murna Muzaifa; Yusya Abubakar; Febriani Febriani; Amhar Abubakar (AGROINTEK, 2023)
Biochemistry of civet coffee fermentation in the digestive tract of civets until now is not fully known. This study aims to isolation, characterization and identification of bacteria molecularly from the civet's digestive tract. Analysis of bacteria begins with the civet surgery to obtain fluid from three parts of the civet's digestive tract. Isolation of bacteria conducted by pour plate method using nutrient agar media. Single and different colonies (shape, colour, margin, elevation, size) were separated and purified by streaking method. The pure isolate was further characterized biochemically. The biochemical characteristics of the bacteria observed were Gram staining,  catalase, protease and pectinase activity. Identification of the bacteria was carried out molecularly by identifying the 16S rRNA gene. The results of molecular identification showed that the bacteria from the civet were identified as Alcaligenes faecalis strain LHW 1749, Ochrobactrum anthropi, Stenotrophomonas sp. 262 and Bacillus sp.